A Content Analysis of Police Report Archives: Basis for Technical Writing Model for Criminology Students - Abaday, Eduardo Castro (Future Science / FSH-PH Publications, 2025)
This research highlights the analysis of data drawn from police report narratives, focusing on the technical words and jargon utilized within these reports. The study examines archival crime investigation documents, employing quantitative content analysis (QCA) to categorize and interpret the language used by law enforcement officers. By defining and classifying recording units—such as specific terms, phrases, and broader themes—the research seeks to understand how these elements contribute to the construction of meaning within criminal justice communication. Two primary questions guide the investigation: (1) What technical words or jargon are reflected in police report narratives? (2) How do these jargon terms shape the interpretation of police reports? Through the examination of a corpus of 20 case reports (comprising 318 pages), the study systematically organizes language into meaningful categories that serve descriptive and statistical purposes. The analysis reveals how officers employ distinct terminology to document case details, enhancing clarity and precision in official records. The study's findings indicate that police report narratives rely on structured terminology to convey critical information about victims, suspects, and investigative processes. These classified terms serve as essential components of law enforcement documentation, reinforcing standardized communication practices within the criminal justice system. Understanding the role and impact of technical jargon in police reports provides insights into how meaning is constructed, interpreted, and applied in investigative contexts.